Greenhouse gas emissions in irrigated paddy rice as influenced by crop management practices and nitrogen fertilization rates in eastern Tanzania - Mboyerwa, Primitiva A.; Kibret, Kibebew; Mtakwa, Peter; Aschalew, Abebe (Frontiers in Sustainable Food Systems, 2022)
Reducing greenhouse gas emission (GHG) from paddy rice production is an important target for many countries, Tanzania inclusive so as to comply with the climate policy commitments. However, there is a dearth of studies on the impacts of crop management practices and nitrogen fertilization on GHG emissions in Tanzania. For successful climate smart rice cultivation, rice management practices and nitrogen fertilization are two key elements required to be studied. The study is focused on impact of crop management practices and nitrogen fertilization on greenhouse gas (GHG) emissions from irrigated paddy rice in field’s conditions. The objectives of this study were a) to assess the effect of different crop management practices and nitrogen fertilization rates on greenhouse gas emissions and b) to determine the optimum nitrogen application rate to increase rice yield while mitigating GHG emissions under system of rice intensification as crop management practice. Experiments were set in split-plot randomized complete block design with three repetitions. Two rice management practices thus conventional practice (CP) and system of rice intensification (SRI) and six levels of nitrogen fertilizer (absolute control, 0, 60, 90,120 and 150 kg N ha−1) were applied in two consecutive seasons. The Source-selective and Emission-adjusted GHG CalculaTOR for Cropland (SECTOR) was used. Methane emission was in the range of 90- 220.7 kg ha-1season-1, where higher emission recorded in CP treatments (ABC, CP 0 and CP 120N) compared to SRI treatments. SRI reduced methane emission for 59.2% over CP. System of rice intensification reduced seasonal carbon dioxide emission by 25% compared to CP. Seasonal nitrous oxide emission was in the range of no detected amount to 0.0002 kgN2O ha-1 where SRI treatments recorded higher emissions over CP. The interaction of system of rice intensification and 90 kg N ha-1 (SRI 90N) treatment recorded higher grains yield (8.1, 7.7 t ha-1) with low seasonal global warming potential (3513.3±4.7, 3479.3 ±1.9 kg CO2e ha-1) and low greenhouse gas intensity (0.43, 0.46 kg CO2e per kg paddy) compared to other treatments in wet and dry season respectively. Therefore, SRI 90 N was the effective mitigation practice for reducing GWP without compromising rice yield.